Identify Fake News: Solutions for Students - Thi Mai Oanh, Lu; Thanh, Nguyen Quy; Binh, Ha Anh (VNU Journal of Science: Education Research, 2024)
Evaluating fake news for factuality is a complex and critical task. This area of research has recently gained significant attention. Our study investigates the link between various factors and the ability to detect fake news, based on a survey of 1161 students from two Vietnamese universities. Most students struggle to discern fake news. To equip students with the tools to combat misinformation, we explore the connection between various factors and the ability to detect fake news. We propose two sets of solutions: individual-level solutions (perception, attitude, and behavior) and system-level solutions (strategic source identification, machine learning, propaganda awareness, and media literacy education). Analysis using the PLS-SEM model shows that the three individual-level solutions significantly contribute to detecting fake news, with a coefficient of determination (R 2 ) of 0.503.